A Longitudinal Study of the Pastures Grazed and Body Condition Scores of Pony Club Horses In one Region of Australia - Buckley, Petra; Morton, John; Buckley, David; Coleman, Glen (Journal of Veterinary Healthcare, 2018)
A cohort of Pony Club horses was observed for 13 months with data collected from owner-kept diaries and monthly property visits. All horses studied had access to pasture for all or part of the day. Whilst paddock size was seldom limiting, pasture degradation was evident and observed pasture mass and composition varied greatly. Horses’ body weight indices and body condition scores also varied greatly, closely matching seasonal variations in pasture mass. Increments in bodyweight varied in a non-linear fashion with body condition score. Most horses experienced additional year-round hand-fed supplementation and half of the study horses recorded body condition scores greater than 3.5 out of 5. This suggests that the owners of Pony Club horses did not rely on pasture as the sole source of nutrition, even though, based on estimated energy demands, well-managed pasture can meet the energy requirements of Pony Club horses. Furthermore, the fact that owners appeared not to make horse feeding decisions based on body condition score resulting in obesity, raises health and welfare concerns in this cohort of horses. The inappropriate feeding of supplements observed during times of high pasture growth was a concern. Whilst the ideal pasture for Pony Club horses has not been described, it is likely to differ to those considered ideal for broodmares and other livestock because of these unique health risks associated with high levels of non-structural carbohydrate content in improved pasture species. This study highlights the need to educate owners about recognising unhealthy body conditions of horses and better managing pastures and pasture access to reduce the risk of obesity related disorders, whilst at the same time reducing pasture degradation and supplemental feed costs
Keywords: Obesity; horse; body condition score; pasture